Boron Removal from Model Waste Water Using Adsorption Process: A Case Study - Zukhri, Syifaa (Universiti Teknologi PETRONAS, 2016)
The separation technologies for boron removal vary from one industry to another depending on the quality of the waste water and the level of boron itself. Adsorption technique is believed to successfully remove boron that exist in low concentration from an aqueous solution. In this paper, the suitability of newly-synthesized geopolymeric adsorbent will be compared with commercial adsorbent, which is activated carbon. The experimental results of pre-adsorption verified that the geopolymer is not suitable to be used as an adsorbent for boron removal purpose hence is discontinued from the adsorption study. The effect of parameters such as dosage, contact time, and initial boron concentration on boron removal using activated carbon were observed. Adsorption isotherm of boron on activated carbon was also investigated to evaluate the adsorption capacity. Adsorption isotherm modeling was conducted based on Langmuir and Freundlich isothemrs.